2017
DOI: 10.1007/s10384-017-0508-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intraocular pressure reduction on progression of normal-tension glaucoma with myopic tilted disc and associated risk factors

Abstract: Lower-percent reduction in IOP was associated with NTG progression in eyes with myopic tilted discs, and the presence of disc hemorrhage was a risk factor for NTG progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The Advanced Glaucoma Intervention Study 24 , Collaborative Normal-Tension Glaucoma Study Group 25,26 , and others 27 have demonstrated that IOP reduction, even when damage has occurred at low IOP, reduces the rate of progressive visual field loss. Yet the absolute level of baseline, unmedicated IOP does not statistically distinguish which patients with OAG will ultimately suffer progressive optic neuropathy, even though patients with the greatest therapeutic IOP reduction ultimately suffer less glaucoma progression 28 . About 20% of such patients experience progressive optic neuropathy five years after 30% IOP reduction from normal baseline levels 3 , even sometimes to such deeply subnormal IOP that ocular hypotension then poses a separate risk of vision loss 29 .…”
Section: Introductionmentioning
confidence: 99%
“…The Advanced Glaucoma Intervention Study 24 , Collaborative Normal-Tension Glaucoma Study Group 25,26 , and others 27 have demonstrated that IOP reduction, even when damage has occurred at low IOP, reduces the rate of progressive visual field loss. Yet the absolute level of baseline, unmedicated IOP does not statistically distinguish which patients with OAG will ultimately suffer progressive optic neuropathy, even though patients with the greatest therapeutic IOP reduction ultimately suffer less glaucoma progression 28 . About 20% of such patients experience progressive optic neuropathy five years after 30% IOP reduction from normal baseline levels 3 , even sometimes to such deeply subnormal IOP that ocular hypotension then poses a separate risk of vision loss 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have failed to establish statistical relationship of IOP to POAG 22,29 or to progressive ON damage [30][31][32] . Even when reduced by treatment, IOP level does not statistically predict progressive ON damage 31,33 , and around 20% of patients develop such damage 5 years after 30% IOP reduction from levels already statistically normal 24 , even when extremely low IOP itself begins to cause visual loss 34 . Clearly, other sources of stress on the ON besides IOP deserve consideration.…”
mentioning
confidence: 99%
“…The relationship between disc tilt or torsion and visual field defect progression is controversial. Some studies did not find any significant association (98)(99)(100)(101). Other studies suggested that the presence of disc tilt and a larger vertical disc tilt angle are protective factors against visual field progression (102, 103).…”
Section: Longitudinal Studiesmentioning
confidence: 99%